Idiopathic normal pressure hydrocephalus– a report of 73 patients. Issue 4 (April 1977) - Greenberg, J O; Shenkin, H A; Adam, R
Abstract : In 1973 we reported results of ventricular shunting in 28 patients with idiopathic normal pressure hydrocephalus. The present report consists of a three year follow-up of the latter (series 1), and an additional 45 patients (series 2) are presented for further insight into the conclusions drawn from the original experiences.